Alterações químicas do solo e resposta do milho à calagem superficial e à adubação nitrogenada realizada na aveia em sistema plantio direto - Feldhaus, Itacir Cesar (2006)
The effects of surface liming and nitrogen application on soil chemical attributes, on the dry matter production of black oats and on the root growth, mineral nutrition and grain yield of corn, under a no-till system, were evaluated in a field trial carried out on a loamy Typic Hapludox, in Ponta Grossa, State of Paraná, Brazil. A randomized complete block, split-plot design was employed, with three replications. The plots received four treatments of lime: no lime, 4, 8 and 12 t ha-1 of dolomitic lime applied on the surface before the sowing of the oats. In the subplots were employed four treatments of nitrogen: without nitrogen, 60, 120 and 180 kg ha-1 of nitrogen spread out manually at tillering of oat plants. After 110 days of the application, liming provided soil acidity correction to a depth of 20 cm, with effects of larger magnitude in the uppermost soil layer (0-5 cm). After 330 days of the application, liming raised pH and reduced the potential acidity (H+Al) to a depth of 20 cm, reduced Al3+ to a depth of 40 cm and raised bases saturation to a depth of 60 cm. The treatments of N promoted acidification of the uppermost soil layers and raised the levels of N-Mineral in the uppermost soil layers 60 days after the application, and in the subsoil 280 after the application. The levels of Ca2+ in the uppermost layers were reduced with N application, but there was no correlation between NO3 - leaching and the amelioration in the subsoil chemical attributes with liming. The dry matter production of oats was not affected by the treatments of liming and N. The root growth of the corn cultivated in succession was also not affected by the treatments. Liming increased the Ca and S levels in the leaves and in the grains of corn, respectively, and reduced the leaf Mn content. The treatments of N fertilization increased the content of N in the grains and of Mn in the leaves and in the grains of corn. Liming had no effect in the dry matter production, grain yield and content of oil and protein of corn. The N treatments had no effect in the dry matter production, but raised the grain yield and the content of oil and protein of corn.